Perebusan Kara Benguk (Mucuna Pruriens) Dan perlengkapan pengaruh toksiknya terhadap struktur kelenjar tiroid tikus putih - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Forty five rats of Rattus norvegicus were divided into 3 groups of 15 each. The first group fed diets containing formula 521, group II fed diets containing formula 521 and fresh Mucuna pruriens with ration 1 : 1, and group III fed diets containing formula 521 and boiled Mucuna pruriens with ration 1 : 1. Each group was killed at 30th day. The results examined from histological changes showed hypertrophy and also hyperplasia of thyroid cells originated from rats fed with fresh Mucuna pruriens. While rats fed with boiled Mucuna pruriens showed vacuolization in the colloid mass of some follicles and dilatation of blood cappillaries. Key words : thyroid gland, rattus norvegicus, mucuna pruriens